The Absorption, Clearance and Metabolic Fate of Dermatan Sulphate Administered to Man - Studies Using a Radioiodinated Derivative - Dawes, J; Hodson, B A; Pepper, D S (Thrombosis and Haemostasis, 1989)
An iodinated derivative of dermatan sulphate was administered by the intravenous, subcutaneous and oral routes to healthy human volunteers in conjunction with unlabelled dermatan sulphate. Following intravenous injection clearance of radiolabel and concentration as measured by competitive binding assay were highly correlated and displayed complex kinetics which were not dose-dependent. Intact 125I-dermatan sulphate was absorbed following both subcutaneous and oral administration, though there appeared to be selective uptake by the gut of a subfraction comprising the smaller or less sulphated molecules. The intact material was subsequently excreted unchanged in the urine. Degradation products of dermatan sulphate were not detected by either gel filtration or affinity chromatography on Polybrene-Sepharose at any time in either plasma or urine, indicating that administered dermatan sulphate is not catabolised by man.
Keywords: Dermatan sulphate; Iodinated derivative; Pharmacokinetics; Absorption; Catabolism